Paternal heterochromatin formation in human embryos is H3K9/HP1 directed and primed by sperm-derived histone modifications - van de Werken, Christine (Nat Commun, 2014)
The different configurations of maternal and paternal chromatin, acquired during oogenesis and spermatogenesis, have to be rearranged after fertilization to form a functional embryonic genome. In the paternal genome, nucleosomal chromatin domains are re-established after the protamine-to-histone exchange. We investigated the formation of constitutive heterochromatin (cHC) in human preimplantation embryos. Our results show that histones carrying canonical cHC modifications are retained in cHC regions of sperm chromatin. These modified histones are transmitted to the oocyte and contribute to the formation of paternal embryonic cHC. Subsequently, the modifications are recognized by the H3K9/HP1 pathway maternal chromatin modifiers and propagated over the embryonic cleavage divisions. These results are in contrast to what has been described for mouse embryos, in which paternal cHC lacks canonical modifications and is initially established by Polycomb group proteins. Our results show intergenerational epigenetic inheritance of the cHC structure in human embryos.